2015
DOI: 10.3928/02793695-20150522-01
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sources of Stress Among First-Year Nursing Students in Jordan

Abstract: The aim of the current study was to determine the most prevalent sources of stress among first-year nursing students at a military college in Jordan. A descriptive cross-sectional study was performed using a convenience sample of 138 students (females between ages 18 and 22). The Student Stress Survey was used to identify stressors and assess their relative importance. The instrument consists of 40 items divided into four categories of potential sources of stress: (a) intrapersonal, (b) interpersonal, (c) acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Many of these sources of stress can be alleviated or eliminated by university management teams by making psychological or psychopedagogical services available to university students (Shudifat & Al‐Husban, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these sources of stress can be alleviated or eliminated by university management teams by making psychological or psychopedagogical services available to university students (Shudifat & Al‐Husban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several authors have pointed to the need to design programs and implement actions aimed at reducing stress and its adverse effects on nursing students | 1287 (Shudifat & Al-Husban, 2015). Although stress in nursing students cannot be eliminated entirely, it can be minimized (Onieva-Zafra et al, 2020;Shudifat & Al-Husban, 2015). Therefore, for nursing faculties to offer quality training, it would be necessary to detect and subsequently prevent the different sources of stress that influence students, thus optimizing the teaching/learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also showed that when students felt stressed, some adopted negative coping strategies, such as showing anger/irritability, engaging in unhealthy eating habits (e.g., consumption of too much food or coffee), or smoking cigarettes. Previous studies have reported that high levels of perceived stress affect eating habits [60] and are linked to poor diet quality, increased snacking, and low fruit intake [61]. Stress in clinical settings has also been linked to sleep problems, substance misuse, and high-risk behaviors' and plays a major role in student's decision to continue in their programme.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque el estrés académico no puede ser eliminado en su totalidad, sí que puede ser minimizado (Arribas, 2013). Por ello, en los últimos años se ha señalado la necesidad de poner en marcha acciones y medidas cuya finalidad sea la reducción del estrés en los estudiantes universitarios (Shudifat y Al-Husban, 2015;Fornés-Vives, et al, 2012). Para que las universidades puedan llevar a cabo programas formativos de calidad, se hace necesario detectar las posibles fuentes de estrés y poner servicios psicológicos o psicopedagógicos a disposición del alumnado universitario (Shudifat y Al-Husban, 2015).…”
Section: Universitat Politècnica De Valènciaunclassified